The Effect of Low Dose of Aspirin on the Preeclampsia in Pregnant Women: A Meta-Analysis - Arianty, Meike; Murti, Bhisma; Budihastuti, Uki Retno (Journal of Maternal and Child Health, 2022)
Background: In 2020 there were 4,627 maternal deaths in Indonesia. Preeclampsia is a complication in pregnancy that occurs 2-8% of all pregnancies and is a major cause of maternal morbidity. Low-dose aspirin has been shown to be a safe and effective primary prevention for the incidence of preeclampsia. With preventive measures can reduce both moral and material losses for patients at high risk for the incidence of preeclampsia. The purpose of this study was to estimate the magnitude of the effect of low-dose aspirin on the incidence of preeclampsia in pregnant women based on previous research. Subjects and Method: This study is a systematic review and meta-analysis. Article searches were conducted using electronic databases such as Google Scholar, PubMed, Cochrane, Science Direct. The articles used are published articles from 2012-2022. The keywords used to search the article were “Aspirin OR Acetylsalicylic Acid AND Prevention AND Pre-Eclampsia OR Toxemia AND Randomized Controlled Trials”. The inclusion criteria used are articles with randomized control trial studies, full text articles are available, the results of the analysis used are Risk Ratio. The population of the study was high-risk pregnant women, the research intervention was the administration of low-dose aspirin, the study comparison was a placebo, and the outcome of the study was preeclampsia, the articles were in English or Indonesian. The article search results are listed in the PRISMA diagram and analyzed using the Review Manager 5.3 application. Results: A total of 7 articles from China, America, India, Congo, Guatemala, Pakistan, and Finland showed that aspirin had an effect of 0.87 times in reducing the incidence of preeclampsia when compared with placebo or no administration (RR = 0.87; 95% CI 0.72 to 1.05). although not statistically significant (p=0.160). Conclusion: Low-dose aspirin affects the incidence of preeclampsia in pregnant women.